In defense of Israel - Hagee, John. (Lake Mary, Fla. : FrontLine, 2007)
Pastor John Hagee calls for Christians to support Israel and explains why, discussing historical Christian anti-Semitism and myths about the Jewish people, presenting answers to Christian and secular critics, and describing his founding of the organization Christians United for Israel.
It's 1938 again -- My lifelong love for Israel -- Sins of the fathers -- "One single night" becomes many -- The peoples of the Middle East -- The religions of the Middle East -- Revolution and radical Islam -- Our debt to the Jewish people -- Honoring Israel brings God's blessing -- Answering Christian critics -- Answering secular critics -- "Israel lives!"
Includes bibliographical references (pages 197-201) and index.
Keywords: Israel (Christian theology); Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Christianity; Interfaith relations; Israel (Christian theology)